KORELASI FIQH DAN SUNNAH MENURUT PEMIKIRAN JAMAL AL-BANA - Farid Adnir (SHAHIH (Jurnal Ilmu Kewahyuan), 2020)
The purpose of this article is to explore Jamal al-Banna's opinion about the correlation between fiqh and sunnah. Basically Fiqh with Sunnah cannot be separated, various kinds of actions carried out by the Prophet Muhammad SAW become the initial resting in the determination of laws relating to fiqh, activities carried out by scientists collect all the rituals and deeds of prophets which are termed on the basis of the Sunnah recorded by the Sunnah Companions when seeing or confronting the Apostle when educating his Companions. According to Jamal Al Banna, the current fiqh is only fiqh that was initiated by the scholars, not the Qur'anic and Sunnah fiqh. Jamal al-Banna divides fiqh into three characters; First justify the Qur'an as a foothold or the main basis for taking legal policy. However, in addressing al-Qur'an, Jamal al-Banna differed from the scholars, the previous interpretation. In fact he will not make their interpretation as the main source, because there is no requirement for taqlid to be blind to their work. Second, have attention to the sunna. According to Jamal al-Banna, the sunna that was recorded by the previous scholars was mostly a sunna that was included in the fake category. Third, Fiqh has attention to wisdom. Outside the Koran and the Sunna, in fact Allah Almighty. also reduce wisdom. God himself also points to who is entitled to wisdom. Wisdom is a treasure of Muslims spread across the world, and it is the duty of Muslims to find and use it as an effort to make fiqh renewal. As for Jamal al-Banna's opinion about the sunnah is the effort and struggle of the Prophet in giving and presenting guidance or guidance, explanatory or tabayyun, and explaining the details of the verses of the Qur'an. Jamal al bana gives a very significant difference if it is related to the phrase or the term Sunnah and Hadith, during this day Islamic thinkers are not too vigorous in giving the difference between these two words, according to him the Sunnah is the path taken by the Prophet Muhammad on his journey when preaching about rituals of Worship , such as prayer, pilgrimage, zakat, fasting and various other rituals, so that the way, the way the Prophet in doing this worship was passed down from generation to generation and followed by the next generation, the Prophet's expression, people who do not follow my sunnah then he is not a part of me, so this sunnah every act that is exemplified by the prophet peace be upon him in worship, behavior and other actions, then according to Jamal the sunnah is closer to the actions carried out by the Prophet Muhammad, then arises the term Sunnah Amaliah, are various methods, concepts or ways that carried out by the Prophet and educate Muslims in various rituals to religion.